2015
DOI: 10.1002/adfm.201404010
|View full text |Cite
|
Sign up to set email alerts
|

Defeating Loss Mechanisms in 1D TiO2‐Based Hybrid Solar Cells

Abstract: Titanium dioxide (TiO2) semiconductors are widely used in energy conversion, energy storage, catalysis, and other electronic applications. Hydrothermally grown TiO2 nanowires are an alternative to mesoporous TiO2 nanostructures due to possible direct charge transport, but their full potential waits to be unleashed. Latest findings show a peculiar defect structure, consisting of small single‐crystalline fingers and free internal surfaces, which supposedly promote a number of loss mechanisms. In this paper, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Previously, we found that the fine structure results from crystal defects in the early growth state and propagates throughout the growth [27]. The additional grain boundaries affect not only the chemical stability but also the electronic properties such as charge carrier mobility [28][29][30][31]. Within a nanorod, these nanofingers merge and form a single crystal for sufficiently high annealing temperatures [32].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that the fine structure results from crystal defects in the early growth state and propagates throughout the growth [27]. The additional grain boundaries affect not only the chemical stability but also the electronic properties such as charge carrier mobility [28][29][30][31]. Within a nanorod, these nanofingers merge and form a single crystal for sufficiently high annealing temperatures [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, devices incorporating these hydrothermally grown TiO2 NW arrays fall short of expectations, which were predicted for highly crystalline 1D materials. [14][15] One reason for the low efficiency of e.g. hybrid solar cells is the high recombination rate of charge carriers due to intrinsic point defects (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wisnet et al used a combination of TiCl4 treatment and annealing of NW arrays to reduce the recombination in hybrid solar cells. 14 Recently, Liu et al proposed a combination of helium ion implantation and subsequent annealing to introduce voids inside rutile TiO2 NWs and thereby they enhanced the photoelectrochemical water splitting. 15 Another approach is the thermal treatment of H2Ti3O7 NWs, which results in voids inside TiO2 NWs.…”
Section: Introductionmentioning
confidence: 99%
“…The high-angle annular dark-field scanning transmission electron microscopy ((S)TEM) images in Figure 2 , all taken from the central part of appropriate NWs, show more significant changes inside the NWs due to the annealing. While the as-grown NW is built by a bundle of nanofibers, as indicated from the SEM image, the annealed NWs are a single-crystalline material, which is interspersed with voids [ 31 , 32 ]. Nevertheless, SEM showed that even for the annealed NWs there are still residuals of the former nanofiber bundle at the tip ( Figure 1 b,c).…”
Section: Resultsmentioning
confidence: 99%